MEMBANGUN SOLIDARITAS DALAM BUDAYA SAIYO SAKATO - Ratih Probosiwi (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2018)
This research looks at the application of Saiyo Sakato culture in the daily life of Minang people, especially in Padang Pariaman. Saiyo Sakato as one of the noble values and original culture of the Minang community. It teaches the value of intergroup unity among the Minang people. The primary data were obtained from in-depth interviews, observations, while the secondary data were collected from library research. The value of intergroup unity among communities is associated with solidarity, that is, togetherness, common interest, and sympathy. The research findings show that as members of the Minang Nan Sakato community, people in Padang Pariaman who live both in villages and in urban areas still uphold the values of togetherness, unity and promote deliberation to reach consensus in community. The role of tetua adat (the elders in charge of adat), tetua lingkungan (the elders in charge of the environment), and religious elders is very strong in maintaining the sustainability of Saiyo Sakato.